Back Cover: Formation of an Isolable Divinylborinium Ion through Twofold 1, 2‐Carboboration between a Diarylborinium Ion and Diphenylacetylene (Angew. Chem. Int. Ed. 19/2017). Issue 19 (4th April 2017) - Tanaka, Naoki; Shoji, Yoshiaki; Hashizume, Daisuke; Sugimoto, Manabu; Fukushima, Takanori
Abstract : The dimesitylborinium ion ("horse"), which is the most electron‐deficient isolable two‐coordinate boron cation, was expected to be transformed into a product with an increased coordination number for the boron atom upon a chemical reaction. However, this boron cation undergoes twofold 1, 2‐carboboration with diphenylacetylene to form another isolable borinium ion ("Pegasus") with an extended π‐conjugated system. This unusual reactivity is described by Y. Shoji and co‐workers in their Communication onpage 5312 ff.